A Bibliometric Analysis of the Journal of King Abdulaziz University: Islamic Economics - توميوانغ، سونسي كارينا (جامعة الملك عبدالعزيز - معهد الاقتصاد الإسلامي, 2023)
مع تزايد الاهتمام بالاقتصاد الإسلامي في الآونة الأخيرة، فإن مجلة جامعة الملك عبدالعزيز: الاقتصاد الإسلامي وهي أول مجلة علمية في هذا التخصص قامت بدور مهم –وما تزال- في تقديم رؤى تتعلق بتطبيق الاقتصاد الإسلامي، وتشكيل تطور أدبياته. بدأت المجلة إصدار أول عدد في عام 1983. وفي عام 2009 تم إدراجها في قواعد بيانات سكوبس (Scopus). تسعى هذه الدراسة إلى تحديد الاتجاهات البحثية المهمة لهذه المجلة، وتتبع التطور الذي حدث فيها منذ إدراجها في قواعد بيانات سكوبس في عام 2009 وحتى 31 أغسطس 2022. من أجل تحقيق هذا الهدف تم فحص 331 مقالة باستخدام برامج إحصائية متخصصة مثل آر استوديو (Rstudio) وفي أو أس فيور (VOSviewer)، ومايكروسوفت إكسل (Microsoft Excel). تشير نتائج الدراسة إلى زيادة عدد المقالات المنشورة والاقتباسات من المجلة. كما تشير النتائج إلى أنه على الرغم من المساهمة الرئيسة للمملكة العربية السعودية في التمويل الإسلامي، وهو البلد الذي تأسست فيه المجلة فإن دولا إسلامية وغير إسلامية كالمملكة المتحدة، والولايات المتحدة ساهمت في تزايد النشر في المجلة. حددت الدراسة أيضا ثماني موضوعات بحثية تناولتها المجلة كالنقاش الفلسفي المتعلق بالربا، ومتانة واستقرار صناعة التمويل الإسلامي خلال فترة الأزمة المالية العالمية، ودعت الدراسة من جهة أخرى الباحثين إلى إجراء المزيد من الدراسات الكمية للكشف عن الأدلة التجريبية للتطبيقات الشائعة في الاقتصاد والتمويل الإسلامي، لاسيما في صناعة الحلال التي أصبحت قطاعا مؤثرا نال اهتماما متزايدا في السنوات القريبة الماضية. كما دعت الدراسة الباحثين إلى الربط في أبحاثهم بين مبادئ الاقتصاد الإسلامي والتوجهات العالمية المختلفة كتغير المناخ وقضايا البيئة بشكل عام. توصي الدراسة في الختام بأن تقوم هيئة تحرير المجلة بترجمة المقالات العربية للغة الإنجليزية لتوسيع نطاق التغطية، وتعزيز مؤشر الاقتباس. With the growing interest and importance of Islamic economics in today's world, the Islamic Economics Journal of King Abdulaziz University, as the first academic journal in this discipline, plays a prominent-and still is playing- an important role in providing insight into current practice and shaping the development of Islamic economic literature. The first issue of the journal appeared four decades ago; in 1983 In 2009 the journal has been indexed by Scopus for the first. This study aims to identify significant trends in this journal and trace its evolution from its first indexation by Scopus in 2009 till August 31, 2022. A total of 331 articles were examined using relevant statistical packages like Rstudio, VOS viewer and Microsoft Excel. The results of this bibliometric analysis suggest that, on average, there is an increasing trend of publications and citation in the journal. Despite the predominance of Saudi Arabia, the home country of the journal, this upward trend is also driven by Muslim minority countries, and non-Muslim countries as well including the United Kingdom and the United States. This study also identified eight major research themes covered by the journal like philosophical discussion on ribā and resilience of Islamic finance industry during global financial crisis; and on the other hand, the study calls for future researchers to conduct more quantitative articles submitted to the journal to uncover empirical evidence of existing Islamic economic and financial practices, particularly the halal industry, which has emerged as an increasingly attractive sector. In addition, future researchers may also consider associating the principles of Islamic economics with various global agendas such as climate change and environmental issues in general.,. Finally, the study also suggests that the journal's editorial board should provide an English translation of Arabic articles in order to expand coverage and improve citation index.
Keywords: الاقتصاد الإسلامي -- التحليل الببليوميتري -- التمويل الإسلامي -- السعودية